The tragedy and grief in Hebrew poetry of the middle ages: הטרגידיה והצער בשירה העברית של ימי הביניים (Journal of the College of Languages (JCL), 2019)
This paper tackles tragedy and grief in the Hebrew poetry of the Middle Ages, as being topics which was transferred to it from Arabic poetry at that time. This came as a result of Hebrew poets quoting images from, and adopting the form and content of the Arabic poem. So, this topic was a prominent feature in the Hebrew poetry of the middle ages. The Hebrew poets focused upon this topic along three trends: poems of lamentation, whether being what are called national lamentation where poets expressed their feelings and grieves because of their remoteness and longing to their homeland, which is Palestine or the sacred land, as they claim; here, Zionist trends were apparent in many poems lamenting Zion and other cities. The other type of poetry which witnessed the topic of tragedy and grief was the lamentation of the “dead people”, such friends and relations, as well as in the poetry of evacuation and salvation which contained a lot of sadness and grief. So, the paper is divided into three sections. Each section tackled one trend of these; as well, there is an introduction which tackled the two terms of tragedy and griefs, in addition to their historical backgrounds in literature .Finally, in the conclusion the most important conclusions and stated.תקציר המחקר זה מטפל בנושא הטרגידה והצער בשירת ימי הביניים,בהיותו אחד הנושאים שנחדרו אליה בהשפעת השירה הערבית,אחרי אימוצם של משוררי ימי הביניים לצורות ותוכני או נושאי השיר הערבי,לכן הנושא זה היה תכונה בולטת ביותר בשירה זו ואולי נמשכה ממנה עד יומנו זה , המשוררים העבריים ריכזו על נושא זה בשלושה כוונים ראשיים ,הם שירי הקינה ,הן מה שנקרא בקינה הלאומית, כשהביעו את תחושותם ,רגשותם וכאובותיהם העמוקות ביותר בגלל התרחקותם וגעגועם לארצם המקורית ,שהיא פלסטין או בית המקדש כמו הם טוענים ,ואילו הסוג השני שהופיעו בו מובני הטרגידיה והצער היה בקינת הנפטרים מהקרובים והידידים,יתר על שירי הגולה והגאולה ,שהיו מלאים ברגשות הצער והבכאבה,על מנת זו המחקר חולק לשושה חלקים לפי שלושת הכוונים אלה,עם הקדמה טיפלנו בה מובני הטרגידיה והצער מבחינה לשונית עם רקע הסטורי למונחים אלה בספרות ,אחר כך המחקר נחתם במסקנות החשובות ביותר שהגיע לה המחקר.